Homer2 deletion alters dendritic spine morphology but not alcohol-associated adaptations in GluN2B-containing N-methyl-D-aspartate receptors in the nucleus accumbens - McGuier, Natalie S.; Padula, Audrey E.; Mulholland, Patrick J.; Chandler, L. Judson (Frontiers in Pharmacology, 2015)
Repeated exposure to ethanol followed by withdrawal leads to the alterations in glutamatergic signaling and impaired synaptic plasticity in the nucleus accumbens (NAc) in both clinical and preclinical models of ethanol exposure. Homer2 is a member of a family of postsynaptic density (PSD) scaffolding proteins that functions in part to cluster NMDA signaling complexes in the PSD, and has been shown to be critically important for plasticity in multiple models of drug and alcohol abuse. Here we used Homer2 KO mice and a chronic intermittent intraperitoneal (IP) ethanol injection model to investigate a potential role for the protein in ethanol-induced adaptations in dendritic spine morphology and PSD protein expression. While deletion of Homer2 was associated with increased density of long spines on medium spiny neurons of the NAc core of saline treated mice, ethanol exposure had no effect on dendritic spine morphology in either wild-type (WT) or Homer2 KO mice. Western blot analysis of tissue samples from the NAc enriched for PSD proteins revealed a main effect of ethanol treatment on the expression of GluN2B, but there was no effect of genotype or treatment on the expression other glutamate receptor subunits or PSD95. These data indicate that the global deletion of Homer2 leads to aberrant regulation of dendritic spine morphology in the NAc core that is associated with an increased density of long, thin spines. Unexpectedly, intermittent IP ethanol did not affect spine morphology in either WT or KO mice. Together these data implicate Homer2 in the formation of long, thin spines and further supports its role in neuronal structure.